Exploration of Innovative Teaching Paths for English Major Courses in Universities on the Intelligent Teaching Environment of Disciplines - Han, Lin (Journal of Educational Research and Policies, 2025)
The smart teaching environment model fully utilizes modern information technology to provide basic support for the development of English curriculum teaching activities. To improve the quality of English major courses in universities, a smart teaching environment system should be established, and the advantages of smart teaching should be leveraged. This article focuses on the concept of a smart teaching environment, explores the application advantages of smart teaching in college English course teaching, designs smart teaching activities, and elaborates on the innovative path of college English major course teaching. The research results indicate that in a smart teaching environment, teachers should fully utilize modern teaching tools, create new teaching models, and improve teaching quality.